Phytochemical Screening and Potency of Mango Peel Extract (Mangifera indica L.) var. Gedong Gincu in Inhibiting the Growth of Staphylococcus aureus - ‘Adawiyah, Robi’atul; Apriyanto, Dadan Ramadhan; Brajawikalpa, Rama Samara (GHMJ (Global Health Management Journal), 2025)
Background: Staphylococcus aureus is a pathogen most of which develop into Methicillin-resistant Staphylococcus aureus. To prevent bacterial resistance, herbal medicine is needed. Mango plants have secondary metabolite compounds that can inhibit bacterial growth. Gedong gincu mango is a specific mango variety that grows widely in Cirebon district. There has been no research that knows the secondary metabolite content and its potential as an antibacterial, especially the peel part which only becomes waste. Aims: To find out the chemical compounds contained and determine the potential of mango peel extract (Mangifera indica L.) var. gedong gincu in inhibiting the growth of Staphylococcus aureus. Methods: This research is an experimental with a posttest only control group design. Phytochemical screening test employed a qualitative method. The extract was made using the maceration method with 70% ethanol solvent. Antibacterial testing with well diffusion method, and given four treatment concentrations (W/V), namely 25%, 50%, 75%, 100%. The measurement on the inhibitory zone after 24 hours at temperature of 370C. Results: Gedong gincu mango peel extract contains secondary metabolite compounds flavonoids, tannins, saponins, and steroids. The inhibitory activity of gedong gincu mango peel extract with a concentration of 25% gedong gincu mango peel extract has an average inhibition zone of 11,55 mm, 50% average inhibition zone 13,55 mm, 75% average inhibition zone 14,88 mm, and 100% average inhibition zone 16,22 mm in inhibiting the growth of Staphylococcus aureus p(<0.05). Conclusion: Mango peel extract var. gedong gincu with a concentration of 25% has the potential to inhibit the growth of Staphylococcus aureus bacteria.